ASSESS THE AWARENESS AND ATTITUDE REGARDING PREVENTION OF CORONAVIRUS DISEASE 2019 - MA, SAHBANATHUL MISSRIYA; HASSAN, SUHAIL (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: Coronavirus disease is the first pandemic caused by a novel coronavirus. The World Health Organization announced a name for the novel coronavirus disease 2019 (COVID-19). This epidemic must stop, contain, control, delay, and reduce the impact of this virus by the people at every opportunity. Every person has the responsibility to contribute, to protect themselves, to protect others, whether in the home, the community, the health-care system, the workplace, or in the transport system. The study was aimed to assess the level of awareness and attitude regarding the prevention of novel coronavirus disease among people and to associate the knowledge level about the prevention of novel coronavirus disease with selected demographic variables of people. Methods: A cross-sectional descriptive design was adopted. Using a convenient sampling technique, 950 samples were selected. The data were collected, analyzed in terms of both descriptive, and inferential statistics. Results: The study results showed that among the total number of people (950) surveyed, 499 (52.6%) were having poor knowledge, whereas 348 (36.6%) were having an average level of knowledge and 103 (10.8%) were showing good knowledge regarding prevention of COVID-19. Some of the people (40.7%) had a negative attitude on the overall aspects of COVID-19 prevention. Conclusion: The study concluded that there were inadequate awareness and poor attitude among the people about coronavirus diseases, and hence there is a need to create awareness through campaigns by public authorities and media.